2020
DOI: 10.1080/07391102.2020.1808077
|View full text |Cite
|
Sign up to set email alerts
|

In-silico screening of plant-derived antivirals against main protease, 3CLpro and endoribonuclease, NSP15 proteins of SARS-CoV-2

Abstract: Novel Coronavirus or SARS-CoV-2 outbreak has developed a pandemic condition all over the world. The virus is highly infectious and spreads by human to human local transmission mode. Till date, there is no vaccination or drugs been approved for the treatment by the World Health Organisation. Henceforth, the discovery of the potential drugs is an urgent and utmost requirement for the medical fraternity. Since, the side effects of plant-derived compounds will be lower compared to synthetic/ chemical drugs. The Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 65 publications
1
32
0
Order By: Relevance
“…As a major compound of SB, scutellarin has exhibited NLRP3 inflammasome suppression, thereby rescuing mice from bacterial sepsis [ 55 ]. In addition, a silico screening report of scutellarin revealed M pro inhibitory effects, supporting our study results [ 56 ]. Meanwhile, baicalein, which is a flavone extracted from the roots of Scutellaria baicalensis and Scutellaria lateriflora , has exhibited notable anti-oxidant, anti-virus, anti-bacteria, anti-inflammatory, anti-cancer, and immunoregulatory effects [ 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 91%
“…As a major compound of SB, scutellarin has exhibited NLRP3 inflammasome suppression, thereby rescuing mice from bacterial sepsis [ 55 ]. In addition, a silico screening report of scutellarin revealed M pro inhibitory effects, supporting our study results [ 56 ]. Meanwhile, baicalein, which is a flavone extracted from the roots of Scutellaria baicalensis and Scutellaria lateriflora , has exhibited notable anti-oxidant, anti-virus, anti-bacteria, anti-inflammatory, anti-cancer, and immunoregulatory effects [ 57 , 58 , 59 ].…”
Section: Discussionsupporting
confidence: 91%
“…The SARS-CoV-2 protein with the top-ranked drug repurposing opportunities was Nsp15. Nsp15 is of particular interest as a drug target because it is an endoribonuclease common to all coronaviruses, is necessary for SARS-CoV-2 replication and interferes with host immune responses ( 51 , 52 , 53 , 54 , 55 , 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using integrated molecular modeling approaches, various reports indicated that phytochemicals such as carvacrol, oleanolic acid, and ursolic acid, might act as probable inhibitors in modulating the M pro protein function and regulating replication of virus [ 129 ]. A computational study has hypothesized that plant-origin compounds viz., bisdemethoxycurcumin, demethoxycurcumin, scutellarin, myricetin, and quercetin could act as possible drug candidates against M pro and NSP15 proteins of SARS-CoV-2 [ 130 ].Further, repurposed existing drugs viz., disulfiram, carmofur, ebselen, shikonin, tideglusib, PX-12, and TDZD-8 might be promising inhibitors targeting M pro [ 131 ]. Similarly, Isavuconazonium (triazole), α-KI (ketoamide), and Pentagastrin (peptide) are suggested as possible drug candidates to treat infected patients with COVID-19 [ 132 ].Currently, several worldwide research organizations and pharmaceutical companies are steadily involved in developing an effective vaccine against the virulent SARS-CoV-2 virus [ 133 ].…”
Section: Cloud Computing Unified Platformsmentioning
confidence: 99%